2020
DOI: 10.1111/mpp.12943
|View full text |Cite
|
Sign up to set email alerts
|

Pm21 CC domain activity modulated by intramolecular interactions is implicated in cell death and disease resistance

Abstract: Molecular Plant Pathology. 2020;21:975-984. | 975 wileyonlinelibrary.com/journal/mpp | INTRODUC TI ONPlants prevent pathogen invasion via a two-layered immune system (Dodds and Rathjen, 2010;Dangl et al., 2013). The first layer is pattern-triggered immunity (PTI) governed by membrane-localized pattern recognition receptors (PRRs). PTI is the basal immune response of plants against infections by pathogens (Couto and Zipfel, 2016;Tang et al., 2017). Once pathogens suppress PTI and enter host cells, plants employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…However, Pm21 originated from the 6AL•6VS translocation of H. villosa. Additionally, wheat varieties carrying Pm21 are reportedly immune and/or highly resistant to the Bgt isolates [21,50]. The many years of eld observations have indicated that GZ1 has a moderate and stable resistance to powdery mildew.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pm21 originated from the 6AL•6VS translocation of H. villosa. Additionally, wheat varieties carrying Pm21 are reportedly immune and/or highly resistant to the Bgt isolates [21,50]. The many years of eld observations have indicated that GZ1 has a moderate and stable resistance to powdery mildew.…”
Section: Discussionmentioning
confidence: 99%
“…Serine and threonine protein kinase genes (including Stpk-V, DvMPK1, DvMLPK, DvUPK, and DvPSYR1) have been located to the Pm21 locus and appear to be required for Pm21-mediated resistance to wheat powdery mildew [17,18]. Recently, the Pm21 gene was cloned and con rmed to encode a single coiled-coil, nucleotide-binding site, leucine-rich repeat protein, in which the coiled-coil domain's activity was closely related to Pm21 resistance to powdery mildew [19][20][21]. Pm56, which resulted from the 6AL•6RS translocation of Secale cereale L. was mapped to the subtelomere region of the arm [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, longer fragment containing further extended sequences outside CC domains may block CC function. In the case of Pm21 (Gao et al, 2020) and Tm‐2 2 (Wang et al, 2020), the CC domain can induce cell death, although the longer CC‐NB‐ARC does not. Interestingly, the converse is true for RPS5, as the CC‐NB‐ARC activates cell death instead of the CC domain (Ade et al, 2007).…”
Section: Cnl CC Domain and Cell Deathmentioning
confidence: 99%
“…Isolated CC domains (Collier et al, 2011; Maekawa et al, 2011; Wang et al, 2015c; Casey et al, 2016; Cesari et al, 2016; Baudin et al, 2017; Kim et al, 2018; Wroblewski et al, 2018; Maekawa et al, 2019; Gao et al, 2020; Wang et al, 2020) and TIR domains (Frost et al, 2004; Swiderski et al, 2009; Krasileva et al, 2010; Bernoux et al, 2011; Williams et al, 2014; Schreiber et al, 2016) from some NLRs can initiate cell death signaling on their own, suggesting that some CC and TIR domains mediate the initiation of immune signaling following NLR activation.…”
Section: Introductionmentioning
confidence: 99%
“…Pm38 and Pm46 are ABC and hexose transporters, respectively. Pm1a , Pm2 , Pm3 / Pm8 / Pm17 , Pm5e , Pm21 , Pm41 , and Pm60 encode immune receptor CNL proteins with nucleotide‐binding sites (NBS) and leucine‐rich repeat (LRR) domains associated with coiled‐coils at the N ‐termini (Gao et al., 2020; Hewitt et al., 2021; Hurni et al., 2013; Li et al., 2020; Sanchez‐Martin et al., 2016; SĂĄnchez‐MartĂ­n & Keller, 2021; Singh et al., 2018; Xie et al., 2020; Yahiaoui et al., 2004, 2009; Zou et al., 2018).…”
Section: Introductionmentioning
confidence: 99%